2015
DOI: 10.20518/tjph.173010
|View full text |Cite
|
Sign up to set email alerts
|

Sakarya İlinde gerçekleşen intihar girişimi vakalarının değerlendirilmesi/Evaluation of suicide attempts in Sakarya

Abstract: Evaluation of suicide attempts in Sakarya AbstractObjective: The objectives of this study were to evaluate the general characteristics, the methods that were used and the causes of suicide attempts for the years of 2009-2010 in Sakarya. Methods: The data were gathered from emergency rooms of all public and private hospitals by using a suicide attempt registration form. All patients (n=1566) admitted to the emergency rooms of the hospitals and who had attempted suicide in the period from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
3
0
3
Order By: Relevance
“…geographical regions and provinces of Turkey. [17][18][19][20][21][22][23][24][25][26][27][28][29] while it is stated that there is no unknown cause, it is estimated that the reason for suicide is unknown in the study of Mete et al in the province of Bingöl of 99 cases (18% of all cases), 30 in the study of Şimşek et al in the province of Manisa of 615 cases (9%), 31 in the study of Goceoglu and Balci in Muğla province of 42 (24%), 32 Bork et al of 89 cases (24.4%) in Elazig province, 33 35 While it is stated in the studies that the reason for suicide is mostly unknown, it is not entered into details and is not included in the statistical analysis, while in the studies of Oğuzhanoğlu et al and Karataş et al it is stated that the relatives of the victims do not want to explain the real reason/reasons of suicide due to the effect of stigma and taboos. 36,37 In the study conducted by Demir in Bursa, it was reported that no data on the cause of suicide could be reached.…”
Section: Inquirymentioning
confidence: 99%
“…geographical regions and provinces of Turkey. [17][18][19][20][21][22][23][24][25][26][27][28][29] while it is stated that there is no unknown cause, it is estimated that the reason for suicide is unknown in the study of Mete et al in the province of Bingöl of 99 cases (18% of all cases), 30 in the study of Şimşek et al in the province of Manisa of 615 cases (9%), 31 in the study of Goceoglu and Balci in Muğla province of 42 (24%), 32 Bork et al of 89 cases (24.4%) in Elazig province, 33 35 While it is stated in the studies that the reason for suicide is mostly unknown, it is not entered into details and is not included in the statistical analysis, while in the studies of Oğuzhanoğlu et al and Karataş et al it is stated that the relatives of the victims do not want to explain the real reason/reasons of suicide due to the effect of stigma and taboos. 36,37 In the study conducted by Demir in Bursa, it was reported that no data on the cause of suicide could be reached.…”
Section: Inquirymentioning
confidence: 99%
“…In order to recognize and prevent this problem, it is important to know the risk factors and protective factors in suicidal behavior. Being between 15-25 years of age, being single, low education level, presence of mental illness or psychiatric diagnosis are some of the risk factors for suicidal behavior (Özel et al, 2008;Önsüz et al, 2012;Arslan et al, 2008;Dilbaz et al, 2005;Yavuz et al, 2006;Şevik et al, 2012;Karamustafalıoğlu et al, 2010;Swan et al, 2002;Fennig et al, 2005;Atay et al, 2012;Kessler et al, 1999). Factors such as commitment to life, satisfaction with health status, help-seeking behavior and social support are protective factors (Atay et al, 2012;Gürkan and Dirik, 2009;Batıgün, 2008).…”
Section: Suicide and Gender: An Evaluation From The Perspective Of Somentioning
confidence: 99%
“…Uluslararası literatürde ölümle sonuçlanan intihar eylemlerinde erkeklerin sık kullandıkları yöntemlerin ateşli silah ve ası; kadınların ise ilaç/madde alımı olduğu bildirilmiştir (8,14). İntihar girişimlerinde ise her iki cinsiyette de sıklıkla anksiyolitikler veya barbitürat grubu ilaçlar kullanıldığı, ayrıca ön kola veya bileğe uygulanan kesme yöntemlerinin ve yüksekten atlama ya da motorlu araç önüne atlamanın da kullanılan yöntemlerden oldukları belirtilmiştir (15)(16)(17)(18)(19)(20)(21)(22)(23). Çalışmamızda da intihar girişiminde kullanılan ilaçların anksiyolitiklerin kullanımı bu sonuçlarla uyumludur.…”
Section: Bulgularunclassified
“…Çalışmamızda intihar nedenleri incelendiğinde; ilk sırada kişilerarası aile içi sorunlarının olduğu göze çarpmaktadır. Ülkemiz genelinde intihar nedenleri içinde ilk üç sırada hastalık, aile içi geçimsizlik ve geçim zorluğu bulunmaktadır (15)(16)(17)(18)(19)(20)(21)(22). TÜİK verilerine baktığımızda ise, bilinen intihar nedenleri 21 22 arasında ilk iki sırayı yine sırasıyla hastalık ve aile geçimsizliği almaktadır.…”
Section: Bulgularunclassified